Human factors testing of the Quanta SC+ hemodialysis system: An innovative system for home and clinic use. Issue 3 (9th April 2019) - Harasemiw, Oksana; Day, Clara; Milad, John E.; Grainger, James; Ferguson, Thomas; Komenda, Paul
Abstract: Introduction: Uptake rates of home hemodialysis are the lowest among all modality types, despite providing patients with clinical and quality of life benefits at a lower cost to providers. Currently, there is a need to develop dialysis systems that are appealing to patients while also being suitable for use across the continuum of care. The SC+ hemodialysis system was developed by Quanta Dialysis Technologies Ltd. to provide patients with a dialysis system that is small, simple to use, and powerful enough to deliver acceptable dialysis adequacy. Methods: As part of the SC+ design validation, human factors testing was performed with 17 Healthcare Professionals (nephrology nurses and healthcare assistants) and 15 Home Users (patients and caregivers). To assess usability and safety, the human factors testing involved between 4.5 and 6 hours of training and, after a period of training decay, a subsequent test session in which participants independently performed tasks on SC+. Findings: Between the two user groups, there were only 29 errors observed out of 1216 opportunities for errors, despite minimal training. Errors that did occur were minor and attributed to an initial lack of familiarity with the device; none were safety related. Discussion: Among prevalent dialysis patients and healthcare professionals, the SC+ hemodialysis system was easy to use, even with minimal training and a learning decay period, and had a high level of use safety. By taking into account human factors to optimize the user experience, SC+ has the potential to address systemic and patient barriers, allowing for wider self‐care and home hemodialysis adoption.